Peran Epistemologi Ilmu Pengetahuan dalam Membangun Peradaban - Mudzakir Mudzakir (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2016)
The formation of a culture in a society, which is based only on one of the scientific dimensions, such as an idea that science is value-free, or that religion is merely a fata morgana, will result in incomplete culture, or even destroy the culture itself. It, on this matter, lies the responsibility of scientists together with other stakeholders to build the nation’s culture. With their expertise, scientists should choose and determine a strategy to integrate moral dimension into scientific ontology, epistemology and axiology. Ontologically, Islam recognizes the existence and truth of āyāt al-kauniyyah as well as āyāt al-qauliyyah and integrates the existence of the two based on faith. Furthermore, the development of the products of Islamic thoughts based on this philosophy form a paradigm system of metaphysical realism based on fundamental concept of tawḥīd (oneness) of the existence of Allah s.w.t., minds and the universe (monism). In the oneness of existence (tawhḥīd), what is meant by science needs a consistent formula in light of the feature of existential oneness. The nature of science seen in this light tends to trigger another scientific activity, i.e. the procedure of finding and developing sciences in religion, within which Allah SWT as a focal point of the thinking framework as well as a reference to the whole existential structure.